Continuum-based approach for modelling the flexural behaviour of plain concrete beam under high-cycle fatigue loads. (15th August 2021) - Xu, Lihui; Ma, Meng; Li, Linfeng; Xiong, Yilei; Liu, Weifeng
Highlights: A continuum-based model for the fatigue behaviours of plain concrete beams was proposed. Computational efficiency was improved by applying jump-in-cycle techniques. Performance degradation only occurs at the midspan of the beam under a three-point bending load. This model provides a basis for modelling the fatigue flexural properties of RC beams. Abstract: In this study, a continuum-based model was proposed to characterise the flexural performance and damage evolution process of a plain concrete beam under high-cycle fatigue loads. The plain concrete beam under three-point bending load was modelled by combining the damaged constitutive model of concrete and the Euler–Bernoulli beam theory with varied stiffness. The dynamic stiffness matrix method, in conjunction with the discretization technique, was adopted to solve the nonlinear governing equations of motion. A global damage index corresponding to natural frequencies was introduced to quantify the performance degradation of the beam. To improve the analysis efficiency of the high-cycle fatigue problems, the accelerated algorithm, namely the jump-in-cycle method, was employed in this model. It is demonstrated that the numerical results agree well with the experimental data under fatigue harmonic loads. Performance degradation under fatigue bending loads only occurs at the midspan of the beam. Adopting the jump-in-cycle methods significantly improves the analysis efficiency of the high-cycle fatigue problem, and the calculation time is reduced by approximately 90% compared with the cycle-by-cycle method. This model is capable of rationally predicting damage evolutions, stiffness degradation processes, stress redistributions, and loading level-fatigue life ( S–N ) curves and can provide a basis for simulating the flexural behaviours of reinforced concrete (RC) beams under fatigue bending loads.